Beyond Self-Care for Helping Professionals : The Expressive Therapies Continuum and the Life Enrichment Model - Hinz, Lisa D.; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
Beyond Self-Care for Helping Professionals is an innovative guide to professional self-care focused not just on avoiding the consequences of failing to take care of oneself, but on optimal health and positive psychology. This new volume builds upon the Expressive Therapies Continuum to introduce the Life Enrichment Model, a strengths-based model that encourages mindful participation in a broad array of enriching experiences. By enabling therapists and other Helping Professionals to develop a rich emotional, intellectual, and creative foundation to their lives and clinical practices, this guide sets a new standard for self-care in the helping professions.
List of Figures; List of Plates; About the Author; Preface 1. Perils of the Helping Professions 2. Beyond Self-Care to Life Enrichment3. The Life Enrichment Model 4. Life Enrichment through Sensation 5. Life Enrichment through Movement 6. Life Enrichment through Pattern and Routine 7. Life Enrichment through Emotion 8. Life Enrichment through Intellect 9. Life Enrichment through Symbolism 10. Life Enrichment through Creativity 11. Living Optimally: A Deep Well, Wide Margins, and Firm Boundaries; References; Index
Includes bibliographical references and index.
Also available in print format.
Keywords: MEDICAL / General; PSYCHOLOGY / Clinical Psychology; Self-care, Health; Caregivers; Care of the sick; Electronic books